Knowledge, Attitude and Practices towards infection prevention among Health Workers in Bugiri Hospital, Bugiri District. A Cross-sectional Study. - Kwagala, Manjeri; Were, Amiri (Student's Journal of Health Research Africa, 2022)
Background: Globally, the incidence of nosocomial infections varies from 3.5% to 12% in developed countries and from 7.5% to 19.1% in low-income and middle-income countries. The purpose of the study was to assess the knowledge, attitude, and practices toward infection prevention among health workers in Bugiri hospital, Bugiri district. Methodology: The study used a cross-sectional study design with a simple random technique as a sampling technique on a sample of 50 respondents. Data was collected using questionnaires with semi-structured and open-ended questions written in the English language; data was later analyzed manually and systematically by compiling it informs of percentages, bar graphs, tables, and piecharts. Results: All (100%) had ever heard about infection prevention, (60%) knew patients as the common sources of infections in health facilities, (68%) knew 20 seconds as the correct minimal time required for hand washing and (58%) knew hand washing with soap and water as the effective standard precaution for infection prevention. (90%) of respondents strongly agreed that they were at risk of acquiring infections, (50%) would feel guilty when they omit hand hygiene precautions, (52%) would not feel free to report safety violation done by their fellow workmates regarding infection preventions, (70%) agreed that they would change working environment due to increased exposure of infections. (64%) regularly use PPE, (and 54%) always wash their hands with soap and water before and after patients care, (76%) had pictorial/ pinned adverts regarding acquired infection prevention measures either to patients or health workers in their departments Conclusion: Knowledge, attitude, and practices of health workers towards infection prevention were equitably delightful despite few noted and observed issues which need to be worked upon by the facility administration to enhance fully infection standard preventive measures. Recommendation: Bugiri hospital administration should provide enough infection prevention facilities and supplies.